Inter- and Intra-Specific Transcriptional and Phenotypic Responses of Pseudo-nitzschia under Different Nutrient Conditions. (18th February 2019) - Lema, Kimberley A; Metegnier, Gabriel; Quéré, Julien; Latimier, Marie; Youenou, Agnès; Lambert, Christophe; Fauchot, Juliette; Le Gac, Mickael
Abstract: Untangling the functional basis of divergence between closely related species is a step toward understanding species dynamics within communities at both the evolutionary and ecological scales. We investigated cellular (i.e., growth, domoic acid production, and nutrient consumption) and molecular (transcriptomic analyses) responses to varying nutrient concentrations across several strains belonging to three species of the toxic diatom genus Pseudo-nitzschia . Three main results were obtained. First, strains from the same species displayed similar transcriptomic, but not necessarily cellular, responses to the experimental conditions. It showed the importance of considering intraspecific diversity to investigate functional divergence between species. Second, a major exception to the first finding was a strain recently isolated from the natural environment and displaying contrasting gene expression patterns related to cell motility and domoic acid production. This result illustrated the profound modifications that may occur when transferring a cell from the natural to the in vitro environment and asks for future studies to better understand the influence of culture duration and life cycle on expression patterns. Third, transcriptomic responses were more similar between the two species displaying similar ecology in situ, irrespective of the genetic distance. This was especially true for molecular responses related to TCA cycle, photosynthesis, and nitrogen metabolism. However, transcripts related to phosphate uptake were variable between species. It highlighted the importance of considering both overall genetic distance and ecological divergence to explain functional divergence between species.